Orientasi Penyusunan dan Wacana Kritis terhadap Tafsir Quran Tematik (TQT) Moderasi Beragama Kementerian Agama - Rosa, Naili (Asosiasi Ilmu Alquran dan Tafsir se-Indonesia, 2022)
This study examines the critical discourse and drafting orientation of the Tafsir Tematik Moderasi Beragama of the Ministry of Religious Affairs. This article analyses the approach taken by the Ministry of Religious Affairs of the Republic of Indonesia in preparing the commentary. It evaluates the approach in terms of linguistic elements, interpretation style, sources of interpretation, methodology, systematics, and critical capacity. Additionally, it explores the author's interpretation tendency (mazhab). By examining the critical discourse pertaining to moderasi beragama as expressed in the tafsir work of a prominent religious institution in Indonesia, this article also seeks to illuminate this institution's efforts in this regard. According to the findings, this tafsir employs the mauḍuʿ interpretation method and is written in the style of adabi ijtimā'i (social society). This interpretation fails to foresee the linguistic elements that constitute the moderation theme. This occurs due to the dense localization in the content of the interpretation, which obscures the presence of the Asbāb al-Nuzūl within the related verses. The development of this interpretation is inextricably linked to the agency's intent and purpose as a response to the continued spread of radicalism in Indonesia.